2011
DOI: 10.1093/annonc/mdq724
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and supplemental intake of one-carbon nutrients and the risk of type I and type II endometrial cancer: a prospective cohort study

Abstract: Background: Type I and II endometrial cancer are biologically and clinically distinct, with type II cancers having a high frequency of p53 mutations and an association with chromosomal instability. This raises the hypothesis that onecarbon nutrients (folate, methionine, and the enzymic cofactors vitamins B2, B6, and B12), which mediate chromosomal stability and DNA methylation, may be protective for type II but not type I endometrial cancer.Methods: Using a prospective cohort of 23 356 postmenopausal women fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
1
32
0
1
Order By: Relevance
“…One study which was restricted to women with type I endometrial cancer demonstrated a null association (Liu et al 2013 ). Another large prospective study demonstrated a similar lack of effect of both dietary and total folate intakes on both type I and type II endometrial cancer (Uccella et al 2011b ). Interestingly, however, this study reported a signifi cantly increased risk of type II endometrial cancer associated with supplemental intakes of folic acid (Uccella et al 2011b ).…”
Section: Endometrial Cancermentioning
confidence: 98%
See 3 more Smart Citations
“…One study which was restricted to women with type I endometrial cancer demonstrated a null association (Liu et al 2013 ). Another large prospective study demonstrated a similar lack of effect of both dietary and total folate intakes on both type I and type II endometrial cancer (Uccella et al 2011b ). Interestingly, however, this study reported a signifi cantly increased risk of type II endometrial cancer associated with supplemental intakes of folic acid (Uccella et al 2011b ).…”
Section: Endometrial Cancermentioning
confidence: 98%
“…The joint effect of vitamin B 6 and the MTHFR 677TT genotype demonstrates the intricate gene-nutrient interactions between one-carbon nutrients and genes involved in the one-carbon transfer reaction pathway. Two prospective studies revealed that vitamin B 6 intakes from diet and supplements were not associated with type I endometrial cancer risk (Liu et al 2013 ) and supplemental intakes, similar to folic acid, was associated with an increased risk of type II endometrial cancer only (Uccella et al 2011b ).…”
Section: Endometrial Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Заболеваемость и биоло-гическая активность РЭ увеличиваются в течение жиз-ни [4,5], что связано с увеличением числа факторов риска.…”
Section: оригинальные статьиunclassified